The image of Islamic boarding schools: An effort to improve through the implementation of public relations - Maulana, Irfan; Supardi, Supardi; Juhji, Juhji; Septiana, Tri Ilma (Adaara: Jurnal Manajemen Pendidikan Islam, 2022)
This study aims to describe the implementation of public relations management in improving the image of Islamic boarding schools. The research method used is a descriptive qualitative case study. This research was conducted at Tarbiyatul Mubtadiin Islamic Boarding School, Pasirnangka Tigaraksa, Tangerang, Banten Province. The informants of this study were the pesantren leaders, the head of the public relations department, the administrators of the pesantren, the teachers' administrators, the students' parents, and the surrounding community: the researcher's research instruments, interview guidelines, and observation guidelines. Data analysis includes data reduction and presentation, as well as concluding. The research results indicate that public relations management at Tarbiyatul Mubtadiin Pesantren Pasirnangka Tigaraksa Tangerang is very influential in improving the image of the pesantren, with a sound management system in the form of planning, implementation, and evaluation. All programs can run according to their original purpose. Public relations management at Tarbiyatul Mubtadiin Islamic Boarding School, Pasirnangka Tigaraksa Tangerang, is very effective both in implementation and the results obtained. Although several challenges and obstacles must be faced, all of them can be overcome with a sound public relations management system to achieve a good image.